Checking whether there is an increased risk of post-transplant lymphoproliferative disorder and other cancers with specific modern immunosuppression regimens in renal transplantation: Protocol for a network meta-analysis of randomized and observational studies - Hutton, Brian; Joseph, Lawrence; Yazdi, Fatemeh; Tetzlaff, Jennifer; Hersi, Mona; Kokolo, Madzouka; Fergusson, Nicolas; Bennett, Alexandria; Buenaventura, Chieny; Fergusson, Dean; Tricco, Andrea; Strauss, Sharon; et al. (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Patients undergoing renal transplant procedures require multi-agent immunosuppressive regimens both short term (induction phase) and long term (maintenance phase) to minimize the risk of organ rejection. There are several drug classes and agents for immunosuppression. Use of these agents may increase the risk of different harms including not only infections, but also malignancies including post-transplant lymphoproliferative disorder. There is a need to identify which regimens minimize the risk of such outcomes. The objective of this systematic review and network meta-analysis of randomized and observational studies is to explore whether certain modern regimens of immunosuppression used to prevent organ rejection in renal transplant patients are associated with an increased risk of post-transplant lymphoproliferative disorder and other malignancies. Methods/design ‘Modern’ regimens were defined to be those evaluated in controlled studies beginning in 1990 or later. An electronic literature search of Medline, Embase and the Cochrane Central Register of Controlled Trials has been designed by an experienced information specialist and peer reviewed by a second information specialist. Study selection and data collection will be performed by two reviewers. The outcomes of interest will include post-transplant lymphoproliferative disorder and other incident forms of malignancy occurring in adult renal transplant patients. Network meta-analyses of data from randomized and observational studies will be performed where judged appropriate based on a review of the clinical and methodological features of included studies. A sequential approach to meta-analysis will be used to combine data from different designs. Discussion Our systematic review will include both single-agent and multi-agent modern pharmacotherapy regimens in patients undergoing renal transplantation. It will synthesize malignancy outcomes. Our work will also add to the development of methods for network meta-analysis across study designs to assess treatment safety. Trial registration PROSPERO Registration Number: CRD42013006951